Efficacy and safety profile of biotechnological agents and Janus kinase inhibitors in VEXAS syndrome: data from the international AIDA Network VEXAS registry - Vitale, Antonio; Caggiano, Valeria; Leone, Flavia; Hinojosa-Azaola, Andrea; Martín-Nares, Eduardo; Guaracha-Basañez, Guillermo Arturo; Torres-Ruiz, Jiram; Kawakami-Campos, Perla Ayumi; Hissaria, Pravin; Callisto, Alicia; Beecher, Mark; Dagna, Lorenzo; et al. (Frontiers in Pharmacology, 2025)
BackgroundVEXAS syndrome, a recently identified systemic autoinflammatory disorder, poses new diagnostic and management challenges. Based on experience with other autoinflammatory diseases, anti-interleukin (IL)-1, anti-IL-6, anti-tumor necrosis factor (TNF) biotechnological agents, and Janus kinase inhibitors (JAKis) have been widely employed in VEXAS patients. The aim of this study is to evaluate the global effectiveness and safety of biotechnological agents and JAKis using data from the real-world context.MethodsClinical, laboratory, and therapeutic data from VEXAS patients were obtained from the international AIDA Network VEXAS registry.ResultsIn total, 69 VEXAS patients were enrolled in the study. Among them, 12 patients (13 treatment courses) received IL-1 inhibitors, 12 patients (13 treatment courses) were administered anti-IL-6 agents, 8 patients (9 treatment courses) were treated with anti-TNF agents, and 16 patients (17 treatment courses) were treated with JAKis. A complete response was observed in 3 patients (23%) treated with anti-IL-1 agents, 2 patients (15%) receiving IL-6 inhibitors, 1 patient (11%) receiving TNF inhibitors, and 4 patients (23.5%) treated with JAKis. The mean prednisone (or equivalent) dosage significantly decreased during anti-IL-1 treatment (p = 0.01), while glucocorticoids changed during anti-IL-6, anti-TNF, and JAKi treatment in a non-significant fashion. A total of 21 patients experienced adverse events, 3 of which led to death (gut perforation, Legionnaires’ disease, and infectious pneumonia) while on JAKis; treatment withdrawal was required for 8 out of 21 patients.ConclusionIL-1 and IL-6 inhibitors, along with JAKis, represent promising therapeutic options for VEXAS patients, albeit careful monitoring is mandatory to control disease activity and ensure safety.